The new 2019-EULAR/ACR classification criteria specific domains at diagnosis can predict damage accrual in 670 childhood-onset systemic lupus erythematosus patients - Pitta, Ana C; Silva, Clovis A; Insfrán, Carlos E; Pasoto, Sandra G; Trindade, Vitor C; Novak, Glaucia V; Sakamoto, Ana P; Terreri, Maria T; Pereira, Rosa MR; Magalhães, Claudia S [UNESP]; Fonseca, Adriana R; Islabão, Aline G; et al. (SAGE Publications, 2021)
Objective: To evaluate if the 2019-European League Against Rheumatism/American College of Rheumatology (EULAR/ACR) criteria at diagnosis of childhood-onset systemic lupus erythematosus (cSLE) are associated with higher rates of early damage scored by Systemic Lupus International Collaborating Clinics/American College of Rheumatology (SLICC/ACR) Damage Index (SDI). Methods: This retrospective multicenter study included 670 cSLE patients with ≤5 years of disease duration. All patients fulfilled both 2019-EULAR/ACR and 1997-ACR classification criteria. Total score of 2019-EULAR/ACR criteria and each of its specific domains were assessed at diagnosis as predictors of damage accrual at the last visit, according to the presence of any organ damage (defined by SDI ≥ 1). Results: Median disease duration was 2.8 (IQR 1.8–3.8) years and 200 (29.9%) patients had at least one organ damage (SDI ≥ 1). The most frequent domains were neuropsychiatric (12%), renal (7%), and musculoskeletal (6%). There was a higher frequency of renal (58% vs 43%, p = 0.0004) and neuropsychiatric domain (21% vs 7%, p < 0.0001) of 2019-EULAR/ACR criteria in patients with damage (SDI ≥ 1) compared to those without damage (SDI = 0). Patients scoring renal or neuropsychiatric domains of the 2019-EULAR/ACR criteria at diagnosis were associated with renal damage (odds ratio 9.701, 95% confidence interval 3.773–24.941, p < 0.001) or neuropsychiatric damage (OR 9.480, 95% CI 5.481–16.399, p<0.0001) at latest visit, respectively. cSLE patients with positive anti-dsDNA at diagnosis were also associated with renal damage by the latest visit (OR 2.438, 95% CI 1.114–5.3381, p = 0.021). Constitutional, hematologic, mucocutaneous, serosal, and musculoskeletal domains and specific criteria as well as other immunologic criteria were not associated with damage accrual. Median of SLEDAI-2K was significantly higher in patients with global damage (19.5 (2–51) vs 14 (0–51), p<0.001). 2019-EULAR/ACR score >25 was associated with more overall (SDI ≥ 1) (38% vs 25%, p = 0.0002) and renal damage (11% vs 5%, p = 0.023). Conclusions: The 2019-EULAR/ACR criteria at diagnosis were associated with a higher rate of early damage in cSLE patients, especially for renal and neuropsychiatric damage. Of note, damage was particularly associated with high disease activity at diagnosis and 2019-EULAR/ACR score >25.
Keywords: 2019-EULAR/ACR criteria; Childhood systemic lupus erythematosus; disease damage; organ damage; SLICC/ACR Damage Index